(3GdMeGjI GdLfGFjI ddTjc (B: s (3OQGSI ebGQfI Hjf GdJTQjY GdeUQi hGdaQfSi hHYV GdOhd GdYQHjI (B/ s - (3fhGd eMeO QTGO YHOGdcQjes; (3ahRjI YHOGdSJGQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2003)
(3Ydi ebOeI Ke HGH JegjOj jMhj JMOjO ehVhY GdHMK K``e Hjf GdTjc hGdChQGb GdJLGQjI , Ke YQVfG dCfhGY GdTHcGJ heG jNVY efgG ddJLQje heG dG jNVY (B. (3hHYO gPG GdJ`j Je JbSje Je JNUjU GdHGH GdChd dOQGSI CMcGe GdTjc (B. - (3ChdG (B: (3CMcGe GdTjc GdLfGFj (B- (3hcGf GdMOjK Yf CQcGf LQjeI (B- (3VhA GdeGOI 337 ef GdQSGdI Edi KdGKI CHhGH (B: (3GdTjc GdJLGQj , Ke EUOGQ Tjc HOhf QUjO(B. (3GdQcf GdeGOj hGdeYfhj aj (B. (3b(B. (3Y (B- (3Ke aj Xd bGfhf GdJLGQI GdLOjO , hYQVfG ddUhQ GdeSJMOKI ddJLQje hjCJj GdHGH GdCNjQ hbO JfGhdfG Hg GdLRGAGJ GdebQQI dMeGjI GdTjc hefgG GdL`RGA GdLfGFj hGdLRGA GdeOfj aj Xd GdJTQjY GdeUQj hGdaQfSj hHYV GdJTQjYGJ GdYQHjI (B- (3hcGfJ GdNGJeI hGdJj JfGhdfG ajgG edNU deG hQO HGdHMK ef CH``hGH haUhd h eHGMK heWGdH Ke Cge GdfJGFL GdJj Je GdJhUd EdjgG ef NdGd GdHMK s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2003s
(3jTJed Ydj EQLGYGJ HdjhLQGajIs
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdJTQjY GdeUQi hGdaQfSis; (3GdMeGjI GdLfGFjIs; (3GdTjcs; (3GdGhQGb GdJLGQjIs; (3GfhGY GdTjcGJs; (3GdfXGe GdSYhOjs; (3GdGOYGA HGdJRhjQs; (3GdMLR Ydi GdQUjOs; (3GdeYGQVI aj GdhaGAs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs